Rancang Bangun Aplikasi Monitoring Kegiatan Menggunakan Metode Prototype - Aditya, Rizky; Pranatawijaya, Viktor Handrianus; Putra, Putu Bagus Adidyana Anugrah (Universitas Palangka Raya, 2021)
Monitoring is an activity that aims to monitor or observe something. In monitoring an activity to be monitored manually, it still has to be monitored directly.The software methodology used for development is the prototype according to Pressman. In this modeling, there are stages, namely Communication, Modeling Quick Design, Construction of prototypes, and Deployment Delivery & Feedback. At this stage of Communication, a Flowchart is made. At the Quick Design stage, the Unified Modeling Language (UML) was made. In the Construction of prototype stage, interface design and programming are made using the Java language.Application Monitoring This activity data storage is created in the online database Firebase Realtime Database as a database, which uses JSON as data parsing, and Android studio is used for application development. There are several features including user login feature, homepage feature, group add feature, map monitoring feature, group attendance feature, member attendance list feature, and user profile feature.